The Impact of Adverse Childhood Experiences (ACEs) on Suicidal Ideation and Suicide Attempts in an Inpatient Adolescent Sample - Benczkowski, Tara; Kostoroski, Christine; Stabile, Mackenzie; Holler, Karen (Adolescent Psychiatry, 2020)
Background: Suicidal ideation (SI) and suicide attempts (SAs) among adolescents are a significant public health concern worldwide. The current study extends previous research by exploring the association between adverse childhood experiences (ACEs) and SI and SAs in a sample of inpatient adolescents as well as identifying specific predictors for increased risk of SI and SAs. Methods: Associations between ACE scores and self-reported SI and SAs were explored in a sample of 154 inpatient adolescents via clinical interview and by analyzing the association between cumulative ACE scores and scores on the Suicidal Tendency scale of a larger personality measure. We also tested for independent relationships between 19 ACEs and SI and SAs to determine unique predictors for suicidality. Results: One-way ANOVA analyses revealed that those who attempted suicide reported significantly more ACEs compared to those who did not attempt suicide. Witnessing violence in the home, school, or neighborhood and experiences of discrimination increased one’s likelihood to attempt suicide by two to threefold, while sexual abuse, neglect, and physical abuse increased this likelihood by three-to-fourfold. Stepwise linear regression analyses demonstrated that emotional abuse, living with someone who had mental health problems or attempted suicide were most associated with elevated Suicidal Tendency scores on a personality measure. Conclusion: Early identification, education and intervention are imperative to limit or eliminate ACEs from occurring. The impact of cumulative as well as specific ACEs on suicide risk should be closely considered as areas for such intervention. Areas for future research include extending to include more diverse populations such as the LGBTQ community as well as more ethnically and racially diverse populations.
Keywords: suicide attempts